Transfer Informasi Intra-Industri: Efek Pengumuman Inisiasi Deviden oleh Perusahaan Reporter - Christina Tri Setyorini (Jurnal Akuntansi dan Bisnis, 2004)
Numerous studies have examined the information content of dividendshypothesis. While much of the empirical evidence indicates that dividend changesconvey unanticipated information to the market, but the effect of the dividend initiationannouncement in the context of intra industry information transfer has not beenextensively examined. This study focus on dividend announcement since the eventsare more likely to be unexpected than subsequent regular dividend announcements.This paper investigates the stock price behavior of rival firm (nonreporterfirm) in the same industry as firm announcing dividend initiation (reporter firm).Using a sample of 32 dividend initiation announcement and 215 nonannouncing firms,spesifically dividend initiation announcement have a significantly impact on thevaluations of industry-related firm. This announcement evoke a contagion (positive)response. This response suggest that industry-related firm view the dividendinitiation as a reflection/signal of favorable firm-spesific corporate development andas a sign of industry-wide condition. Market response to dividend initiations areexamined using event study methodology. To reduce bias effects on Jakarta StockExchange as a thin market, this study using Fowler and Rorke 4 lag, 4 lead to correctthe beta.This study also empirically test the influence of dividend surprise, size andlevel of competition in industry to the security price reaction of nonannouncing firm.Furthermore, the level of competition in the industry, as measured by HerfindahlIndex, has a negative effect to nonreporter’s abnormal return.In sum, dividend initiation announcement has a rich information content notonly for the firm making the announcement but also for other firms in the industry. Inexamining how investors of industry- related firm react to these announcement, thisstudy sheds light on the nature of intra-industry information transfers and the investorpsychology driving these reactions.